2020
DOI: 10.1155/2020/8885169
|View full text |Cite
|
Sign up to set email alerts
|

Study on Three Sarcocapnos Species as Potential Sources of Bioactive Compounds: Relation between Phenolic Content and Bioactivity by Multivariate Analysis

Abstract: In this work, we report the phenolic composition and bioactivity of the aerial parts of three species of Sarcocapnos (S. enneaphylla, S. pulcherrima, and S. saetabensis) to study their potential as sources of bioactive compounds to revalorize them and contribute to the conservation of these plant species. Samples were collected in different locations in the province of Jaén (southeast of Spain), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…S. fistula had the highest total polyphenolics content and it was observed that when considering the total content of all bioactive compounds without kaempferol-3-glucoside, A. fistula also recorded the highest total individual content (35,499.35 µg/g), which might significantly reflect on its highest antioxidant activity in most assays (5/6). This was in agreement with previous reports that demonstrated a good correlation between total bioactive compounds and antioxidant activity [ 17 , 27 , 28 ]. Moreover, many of the identified compounds in the present study were well known for their high antioxidant activity, such as epicatechin [ 29 ], caffeic acid [ 30 ], glycosides of kaempferol [ 31 ], delphindin 3,5 diglucoside [ 32 ], catechin [ 33 ], cinnamic acid [ 34 ], and hyperoside [ 35 ] among others.…”
Section: Resultssupporting
confidence: 94%
“…S. fistula had the highest total polyphenolics content and it was observed that when considering the total content of all bioactive compounds without kaempferol-3-glucoside, A. fistula also recorded the highest total individual content (35,499.35 µg/g), which might significantly reflect on its highest antioxidant activity in most assays (5/6). This was in agreement with previous reports that demonstrated a good correlation between total bioactive compounds and antioxidant activity [ 17 , 27 , 28 ]. Moreover, many of the identified compounds in the present study were well known for their high antioxidant activity, such as epicatechin [ 29 ], caffeic acid [ 30 ], glycosides of kaempferol [ 31 ], delphindin 3,5 diglucoside [ 32 ], catechin [ 33 ], cinnamic acid [ 34 ], and hyperoside [ 35 ] among others.…”
Section: Resultssupporting
confidence: 94%